A Review of MR Spectroscopy Studies of Pediatric Bipolar Disorder - Kondo, D.G.; Hellem, T.L.; Shi, X.-F.; Sung, Y.H.; Prescot, A.P.; Kim, T.S.; Huber, R.S.; Forrest, L.N.; Renshaw, P.F. (American Journal of Neuroradiology, 2014)
Pediatric bipolar disorder is a severe mental illness whose pathophysiology is poorly understood and for which there is an urgent need for improved diagnosis and treatment. MR spectroscopy is a neuroimaging method capable of in vivo measurement of neurochemicals relevant to bipolar disorder neurobiology. MR spectroscopy studies of adult bipolar disorder provide consistent evidence for alterations in the glutamate system and mitochondrial function. In bipolar disorder, these 2 phenomena may be linked because 85% of glucose in the brain is consumed by glutamatergic neurotransmission and the conversion of glutamate to glutamine. The purpose of this article is to review the MR spectroscopic imaging literature in pediatric bipolar disorder, at-risk samples, and severe mood dysregulation, with a focus on the published findings that are relevant to glutamatergic and mitochondrial functioning. Potential directions for future MR spectroscopy studies of the glutamate system and mitochondrial dysfunction in pediatric bipolar disorder are discussed. ACCanterior cingulate cortexATPadenosine triphosphateBDbipolar disorderGABAγ-aminobutyric acidGlnglutamineGluglutamateHChealthy controlsPCrphosphocreatinePiinorganic phosphatetCholtotal choline